AB101. Therapeutic effect of low intensity pulsed ultrasound in stress urinary incontinence - Yang, Bicheng (Transl Androl Urol, 2016)
OBJECTIVE: Stress urinary incontinence, a major type of urinary incontinence, increases with age and is often developed after partum injury. Low intensity pulsed ultrasound (LIPUS) has been investigated in the treatment of many diseases showing its ability of restoring soft tissue injury. We investigated the therapeutic effect of low intensity pulsed ultrasound in stress urinary incontinence. METHODS: Thirty-two Sprague Dawley rats in SUI group underwent vaginal distension (VD) and bilateral ovariectomy mimicking partum injury. Eight rats served as mock operation control. Eight rats each in SUI group was treated with low-dosage LESW (0.03 mJ/mm(2)), medium-dosage LESW (0.06 mJ/mm(2)), or high-dosage LESW (0.09 mJ/mm(2)). The rest eight rats served as none-treatment group. For functional study, leak point pressure test (LPP) was performed 2 weeks after the last LESW. Masson trichrome staining was performed to validate the pathological changes. RESULTS: The LPP was restored in medium-dosage LESW and high-dosage LESW groups, but not in low-dosage LESW group. More robust striated muscle regeneration was found in these two groups comparing with the none-treatment group. CONCLUSIONS: LIPUS ameliorate the symptom of SUI via activating striated muscle regeneration.